2019
DOI: 10.1186/s43093-019-0001-9
|View full text |Cite
|
Sign up to set email alerts
|

Capital inflows, exchange rate and agricultural output in Nigeria

Abstract: The study applied the autoregressive distributed lag (ARDL) technique in investigating the effect of capital inflows and exchange rate on agricultural output in Nigeria between the periods 1981 and 2016. The technique was selected because the variables are integrated at both 1(1) and 1(0) and the sample size is considerably small. Variables used in the study are agricultural output (AO), private capital inflow (PRCI), public capital inflow (PUBCI), investment (INV), labor (L) and real effective exchange rate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The null of no cointegration is rejected if the values of the F-statistics are above the upper critical value (F-Statistics > I(1) value), which indicates the existence of cointegration among the variables and represents a long-term relationship in the model. In contrast, if the F-statistics are less than the critical value of the lower bound I(0), this depicts the null hypothesis of the absence of a long-term relationship [45]. Hjazeen et al [47] estimated the UECM ARDL model for economic growth, stating that once the cointegration relationship was established, one can proceed to the ARDL ECM (error correction terms) model calculations to investigate the relationship among the variables and determine which influential variables affect the dependent variable in the short-and long-term estimations [48].…”
Section: Ardl Cointegration Testing In the Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…The null of no cointegration is rejected if the values of the F-statistics are above the upper critical value (F-Statistics > I(1) value), which indicates the existence of cointegration among the variables and represents a long-term relationship in the model. In contrast, if the F-statistics are less than the critical value of the lower bound I(0), this depicts the null hypothesis of the absence of a long-term relationship [45]. Hjazeen et al [47] estimated the UECM ARDL model for economic growth, stating that once the cointegration relationship was established, one can proceed to the ARDL ECM (error correction terms) model calculations to investigate the relationship among the variables and determine which influential variables affect the dependent variable in the short-and long-term estimations [48].…”
Section: Ardl Cointegration Testing In the Modelmentioning
confidence: 98%
“…The ARDL model for testing cointegration (the ARDL bounds test) was employed to examine the model [44], whether the variables were stationer at level or the first difference (I(0) or I(1)) or mutually cointegrated (I(0) and I(1)), allowing for the simultaneous testing of the long-term and short-term relationships among them. The application of the ARDL bounds tests involved testing for the presence of a long-term relationship, in this study, based on the log linear form, by using the dynamic unrestricted error correction model (UECM) to integrate the short-term relationship with the long-term equilibrium [44,45]. To determine the long-term relationship, we referred to the extensive work of the authors of Nagawa [46], who elucidated the existence of cointegration in the UECM model by checking the null hypothesis of no cointegration (H0: α1 = α2 = α3 = α4 = 0), which was tested against the alternative cointegration (Ha: α1 ̸ = α2 ̸ = α3 ̸ = α4 ̸ = 0).…”
Section: Ardl Cointegration Testing In the Modelmentioning
confidence: 99%
“…It is also true that due to the preponderance of low income among the farmers, it would be difficult to accumulate enough financial resources required to revamp the agricultural sector from revenue generated internally from the sector. It is important to note that the United Nations Food and Agricultural Organization estimated that developing countries need about USD 83 billion annual investment in the agrarian sector to meet their food requirement (Okpe & Ikpesu, 2019). Meanwhile, it has been reported that Nigeria is among the top recipients of migrant workers' remittances in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the exchange rates in Nigeria did not explicitly consider mean-reversion. Instead, they viewed the exchange rate as a macroeconomic variable and its impact on economic growth(see Oloyede and Fapetu, 2018;Ikpesu and Okpe, 2019) while others dwelled on its short-term forecasting(see Nyoni, 2018;Ejem and Ogbonna, 2019). Also, some studies considered its effect on the financial dollarization and remittance inflows (see Udoh and Udeaja, 2019;Adejumo and Ikhide, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the literature focuses mainly on using cointegration approaches to investigate the relationships between exchange rates and other macroeconomic variables. See (Ikpesu and Okpe (2019); Adejumo and Ikhide (2019); Oloyede and Fapetu (2018); Udoh and Udeaja (2019) and Nyoni (2018).…”
mentioning
confidence: 99%